Pengaruh Sistem Pengendalian Internal Pemerintah, Good Governance, dan Komitmen Organisasi Terhadap Kinerja Manajerial (Pada Kecamatan Baleendah Kabupaten Bandung) - Sunjaeni, Marisa; Berliani, Kartika (JUDICIOUS, 2024)
In the current era of regional autonomy, every local government is required to realize good and clean governance. The managerial performance of government agencies is currently in the public spotlight. People who receive services from government agencies begin to question their performance in carrying out their duties as public servants. The research method used is a quantitative method with a descriptive and verifiable approach. The data used in this study is primary data obtained from the results of a questionnaire distributed to 92 employees of Baleendah sub-district, Bandung Regency. The sampling technique is Non-probability Sampling using a saturated sampling approach. To measure the magnitude of the influence of independent variables on dependent variables, classical assumption tests, multiple linear regression tests, Pearson product moment coefficient tests, determination coefficient tests and hypothesis testing were partially and simultaneously used using. This study aims to determine the influence of the Government Internal Control System (X1), Good Governance (X2), Organizational Commitment (X3) and Managerial Performance (Y) in Baleendah District, Bandung Regency. Based on the respondents' answers, it is expected to increase employee involvement, maximize their contribution to the delivery of Information and Communication, provide equal treatment to the community and increase a sense of loyalty and totality towards their workplace.